Physicochemical and Biological Performance of Aloe Vera-Incorporated Native Collagen Films - Mireia Andonegi; Ainhoa Irastorza; Ander Izeta; Koro de la Caba; Pedro Guerrero (MDPI AG, 2020)
Collagen was obtained from porcine skin by mechanical pretreatments with the aim of preserving the triple helix structure of native collagen, which was indirectly corroborated by differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR) results. Moreover, aloe vera (AV), with inherent biological properties, was incorporated into collagen film formulations, and films were prepared by compression and characterized to assess their suitability for biomedical applications. SEM images showed that the fibrillar structure of collagen changed to a rougher structure with the addition of AV, in accordance with the decrease in the lateral packaging of collagen chains observed by XRD analysis. These results suggested interactions between collagen and AV, as observed by FTIR. Considering that AV content higher than 20 wt % did not promote further interactions, this formulation was employed for biological assays and the suitability of AV/collagen films developed for biomedical applications was confirmed.